In Vitro Cross-Linking MS Reveals SMG1-UPF2-SMG7 Assembly as Molecular Partners within the NMD Surveillance - Padariya, Monikaben; Vojtesek, Borivoj; Hupp, Ted; Kalathiya, Umesh (International journal of molecular sciences, 2024)
mRNAs containing premature stop codons are responsible for various genetic diseases as well as cancers. The truncated proteins synthesized from these aberrant mRNAs are seldom detected due to the nonsense-mediated mRNA decay (NMD) pathway. Such a surveillance mechanism detects most of these aberrant mRNAs and rapidly destroys them from the pool of mRNAs. Here, we implemented chemical cross-linking mass spectrometry (CLMS) techniques to trace novel biology consisting of protein-protein interactions (PPIs) within the NMD machinery. A set of novel complex networks between UPF2 (Regulator of nonsense transcripts 2), SMG1 (Serine/threonine-protein kinase SMG1), and SMG7 from the NMD pathway were identified, among which UPF2 was found as a connection bridge between SMG1 and SMG7. The UPF2 N-terminal formed most interactions with SMG7, and a set of residues emerged from the MIF4G-I, II, and III domains docked with SMG1 or SMG7. SMG1 mediated interactions with initial residues of UPF2, whereas SMG7 formed very few interactions in this region. Modelled structures highlighted that PPIs for UPF2 and SMG1 emerged from the well-defined secondary structures, whereas SMG7 appeared from the connecting loops. Comparing the influence of cancer-derived mutations over different CLMS sites revealed that variants in the PPIs for UPF2 or SMG1 have significant structural stability effects. Our data highlights the protein-protein interface of the SMG1, UPF2, and SMG7 genes that can be used for potential therapeutic approaches. Blocking the NMD pathway could enhance the production of neoantigens or internal cancer vaccines, which could provide a platform to design potential peptide-based vaccines.
Keywords: sekundární struktura proteinů; UPF2; messenger RNA; SMG1; protein stability; Nonsense Mediated mRNA Decay; RNA-helikasy; NMD; Codon, Nonsense; mutace; nesmyslný kodon; RNA Helicases; mRNA; Mutation; RNA, Messenger; nonsense mediated mRNA decay; Protein Structure, Secondary; cross-linking; cancer mutations; mass spectrometry; SMG7